Study of Ce(III) as a potential corrosion inhibitor of Zn-Fe sacrificial coatings electrodeposited on steel. (15th May 2022) - Arrighi, C.; Nguyen, T.T.; Paint, Y.; Savall, C.; Coelho, L.B.; Creus, J.; Olivier, M.-G.
Abstract: The effect of Ce(III) on the top surface and galvanic corrosion of ZnFe coating electrodeposited on steel was investigated. The inhibition performance was assessed by Electrochemical Impedance Spectroscopy on the surface of the Zn and ZnFe electrodeposited coatings. The ZnFe/steel galvanic coupling was investigated based on a model coupling studied from the polarization curves while Scanning Vibrating Electrode Technique gave information on a cut-edge configuration. Cerium increases the corrosion of zinc in a galvanic coupling with steel. Inhibitive species decrease the activity of ZnFe during cut-edge corrosion and has an influence on the precipitation products and their localization. Highlights: ● Study of the top-surface and cut-edge corrosion of ZnFe electrodeposited steel ● Cerium accelerates zinc corrosion when coupled with steel ● Cerium reduces the corrosion of ZnFe coated steel cut-edge ● Precipitation pattern on cut-edge is modified in presence of the inhibitive species